Strategi Manajemen Perpustakaan Digital untuk Meningkatkan Kualitas Akademik - Achadi Budi Santosa; Sukirman Sukirman; Subaidi Subaidi (Kelola: Jurnal Manajemen Pendidikan, 2022)
As a supporting unit for achieving higher education quality, for many years the university library has been part of the scientific information ecosystem, and the final form of the university library has turned into a digital library. The purpose of this study is to reveal library management in supporting the quality of academic development in tertiary institutions, as well as the advantages and disadvantages of implementing library management which has been carried out so far in the digitalization era. This study uses a qualitative method. The main subjects of this study were library staff, students, and lecturers. Data collection techniques are through interviews and document analysis, while data validity is carried out through triangulation techniques. The results of the study show that college libraries have changed a lot, and the use of digital technology has become an option for the convenience of academic services. However, the management of digital libraries is still faced with the problem of the limited ability of managers in the field of information technology, low budget allocations, and decreased number of visitors. On the other hand, library operations have also not been able to guarantee digital data security.